Security topology in wireless sensor networks with routing optimisation - Ismail, M.; Sanavullah, M.Y. (2008 Fourth International Conference on Wireless Communication and Sensor Networks, 2008)
Multiple sensor nodes deployed in a common neighborhood to sense an event and subsequently transmit sensed information to a remote processing unit or base station, has been the recent focus of research. Tiny sensor nodes, which consist of sensing, data processing, and communicating components, leverage the idea of sensor networks based on collaborative effort of a large number of nodes. These numerous sensors are used (similar to different sensory organs in human beings) for delivering crucial information in real-time from environments and processes, where data collection is impossible previously with wired sensors [1]. Typically, wireless sensor networks are composed of low power sensor nodes and integrate general-purpose computing with heterogeneous sensing and wireless communication. Their emergence has enabled observation of the physical world at an unprecedented level of granularity. One of the most important components of a sensor node is the power unit and may be supported in most applications by a power scavenging unit such as solar cells. Hence, there is a major limitation in a wireless sensor networks, such as, the sensor nodes must consume extremely low power. Also, wireless networks are subject to various kinds of attacks and wireless communication links can be eavesdropped on without noticeable effort and communication protocols on all layers are vulnerable to specific attacks. In contrast to wire-line networks, known attacks like masquerading, man-in-the-middle, and replaying of messages can easily be carried out. Hence, a fundamental issue in the design of wireless sensor networks is the reliability i.e. how long can the wireless sensor networks survive and how well are the wireless sensor networks recovery after the malicious attacks. In this context, in this thesis, the power, mobility, and task management planes that can monitor the power, movement, and task distribution among the sensor nodes are proposed. These planes help the sensor nodes coordinate the sensing task and also lower the overall power consumption. In addition, a secure topology discovery algorithm is proposed and its performance is studied for different types of node distributions. The proposed work is the development of architecture for secure communication in mobile wireless networks. The approach divides the network into clusters and implements a decentralized certification authority. Decentralization is achieved using threshold cryptography and a network secret that is distributed over a number of nodes. While this basic idea has been proposed earlier partially, its application on a clustered network is a novelty.